Continuity of Urban Structures between Antiquity and Middle Ages in Croatia - Jurković, Miljenko; Maraković, Nikolina; Turković, Tin (2007)
The development of urban structures on the Eastern Adriatic coast has been a topic of research for more than two hundred years. New scientific methods and recent archaeological research, conducted by experts in different disciplines, has made a considerable progress in understanding of town and its continuity, from Antiquity to the middle ages. This presentation is a short synthesis of wide area of research, and an attempt of incorporation of Croatian art historic research into European research area.
Projekt MZOS
ENG